High-Oxygen Submersion Fetal Thymus Organ Cultures Enable FOXN1-Dependent and -Independent Support of T Lymphopoiesis - Han, Jianxun; Zúñiga-Pflücker, Juan Carlos (Frontiers in Immunology, 2021)
T cell development is effectively supported in fetal thymus organ cultures (FTOCs), which places thymus lobes atop an air-liquid interface (ALI) culture system. The direct exposure to air is critical for its success, as fetal thymus lobes placed in low oxygen submersion (LOS)-FTOCs fail to support thymocyte development. However, submersion cultures performed in the presence of high concentration of ambient oxygen (60% ~ 80%) allow for normal thymocyte development, but the underlying mechanism for this rescue has remained elusive. Here, we show that FOXN1 expression in thymic epithelial cells (TECs) from LOS-FTOCs was greatly reduced compared to conventional ALI-FTOCs. Consequently, the expression of important FOXN1 target genes, including Dll4 and Ccl25, in TECs was extinguished. The loss of DLL4 and CCL25 interrupted thymocyte differentiation and led to CD4+CD8+ cells exiting the lobes, respectively. High oxygen submersion (HOS)-FTOCs restored the expression of FOXN1 and its target genes, as well as maintained high levels of MHCII expression in TECs. In addition, HOS-FTOCs promoted the self-renewal of CD4-CD8-CD44-CD25+ cells, allowing for the continuous generation of later stage thymocytes. Forced FOXN1 expression in TECs rescued thymocyte developmental progression, but not cellularity, in LOS-FTOCs. Given that oxidative stress has been reported to accelerate the onset of age-associated thymic involution, we postulate that regulation of FOXN1 by oxygen and antioxidants may underpin this biological process.